The Relationship between Discipline and Learning Motivation and the Science Learning Achievement of State Junior High School Students in Luwu Regency - Fadhilah Utami A; Firdaus Daud; Halimah Husain; Muhiddin Palennari; Muhammad Arsyad (Postgraduate, University of Mataram, 2026)
This study analyzes the levels of discipline, learning motivation, and science achievement among state junior high school students in Luwu Regency, as well as their relationships both partially and simultaneously. The research uses a quantitative non-experimental design with a correlational survey approach, involving 125 students selected through proportional random sampling. Data were collected using Likert-scale questionnaires and documentation, then analyzed with descriptive statistics and linear regression. The results show that discipline (79.89), learning motivation (148.38), and science achievement (75.62) are all in the moderate category. Inferential analysis indicates that discipline has a positive and significant effect on science achievement (57.20%), while learning motivation has a stronger contribution (72.70%). Simultaneously, both variables contribute 78.50% to science achievement. In conclusion, discipline and learning motivation significantly influence science learning outcomes. Improving both in a balanced and integrated way is essential to achieve optimal student performance.